Sustainable Development and Social, Ecological, and Economic Transformation in Vietnam: Insights for Policy - Spangenberg, Joachim (VNU Journal of Science: Policy and Management Studies, 2019)
Abstract : Vietnam is at crossroads: being a middle income country now, it has to deal with social, economic and environmental challenges better known from affluent countries, while still being in the transition from an agricultural to an industrial in a society transiting from rural to urban. At the same time, Vietnam has to prepare for the diverse impacts of climate change, a process beyond its control, by developing adaptation measures safeguarding the social and environmental basis of the society and economy. This requires strategic planning with a focus on enhancing the resilience of economy and society; supporting differentiation and diversity is a core element of this, in rural as much as in urban settings. Current policies need to be updated to accommodate both the value of diversity, and the long term perspective required to mitigate climate change impacts. Keywords: Vietnam, Social Ecological and Economic Transformation, polarisation, industrialisation, urbanisation, market risks, environmental threats. References [1] United Nations General Assembly, Transforming our world: the 2030 Agenda for Sustainable Development, Resolution 70/1 adopted by the General Assembly on 25 September 2015. Document A/RES/70/1. United Nations, New York, 17th session, Agenda items 15 and 116, 2015. [2] J. Weeks, N. Thang, R. Roy, J. Lim, Seeking Equity within Growth. The Asia-Pacific Regional Programme on Macroeconomics of Poverty Reduction. UNDP Regional Bureau for Asia and the Pacific. Ha Noi, 2004. [3] P.M. Hoai, Z. Sebesvari, T.B. Minh, P.H. Viet, F.G. Renaud, Pesticide pollution in agricultural areas of Northern Vietnam: Case study in Hoang Liet and Minh Dai communes, Environmental Pollution 159(12) (2011) 3344-3350. [4] Worldbank, PovcalNet, http://iresearch.worldbank.org/Povcal.Net/index.htm?0, accessed September 6th, 2016. [5] P. Daum, Reisfelder zu Golfplätzen, Le Monde diplomatique 2019(2)(2019) 14-15. [6] C. Bonnin, S. Turner, At what price rice? Food security, livelihood vulnerability, and state interventions in upland northern Vietnam, Geoforum 43(1)( 2012) 95-105. [7] C.A. Howie, Dike Building and multiple rice crops in An Giang Province, Vietnam: benefits, losses and future risks? Paper presented at the ESP Conference Bali, Indonesia, August 26th - 30th, 2013, Ecosystem Services Partnership ESP 2013. [8] N.M. Hue, P.A. Chi, Y. Matsui, Contribution of Quality Management Practices to Sustainability Performance of Vietnamese Firms, Sustainability 10 (2) (2018) 375. https://doi.org/10.3390/su10020375. [9] J.A. Schumpeter, The Instability of Capitalism, The Economic Journal 38(1928) 361-386. [10] T. Piketty, Capital in the Twenty-first Century, Harvard University Press, Boston, USA, 2014. [11] Vietnam Investment Review May 27 -June 2, Focus "Sustainable actions", 1 (2019) 4-21. [12] KOPO, Smart Grids: Was kosten die intelligenten Netze der Zukunft?, Kommunalpolitische Blätter 14.06., 2012. https://kopo.de/blog/2012/06/14/smart-grids-was-kosten-die-intelligenten-netze-der-zukunft/, accessed June 20th, 2019. [13] UBA Umweltbundesamt (Federal Environment Agency), Emissionen des Verkehrs. https://www.umweltbundesamt.de/daten/verkehr/emissionen-des-verkehrs#textpart-1 of May 31st, 2019, accessed July 20th, 2019. [14] IPBES Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services, Brondizio, E.S., Díaz, S., Settele, J., The IPBES Global Assessment on Biodiversity and Ecosystem Services, Secretariat of the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services, Bonn, Germany, 2019. [15] T. Klotzbücher, A. Marxen, D. Vetterlein, J. Schneiker, M. Türke, N. van Sinh, N.H. Manh, H. van Chien, L. Marquez, S. Villareal, J.V. Bustamante, R. Jahn, Plant-available silicon in paddy soils as a key factor for sustainable rice production in Southeast Asia, Basic and Applied Ecology 16(8)( 2015) 665-673. [16] L.E. Erban, S.M. Gorelick, H.A. Zebker, S. Fendorf, Release of arsenic to deep groundwater in the Mekong Delta, Vietnam, linked to pumping-induced land subsidence, Proceedings of the National Academy of Sciences 110(34)(2013) 13751-13756. [17] T.A. Ha, K.M. Thuy, N.T. Thu, N.N. Tung, N.Q. Trung, Methane, Nitrous Oxide and Ammonia Emissions from Livestock Farming in the Red River Delta, Vietnam: An Inventory and Projection for 2000–2030. Sustainability 10(10), (2018) 3826. https://doi.org/10.3390/su10103826 [18] J.H. Spangenberg, A.L. Beaurepaire, E. Bergmeier, B. Burkhard, Ho Van Chien, Le Quoc Cuong, C. Görg, V. Grescho, Le Huu Hai, K.L. Heong, F.G. Horgan, S. Hotes, A. Klotzbücher, T. Klotz¬bücher, I. Kühn, F. Langerwisch, G. Marion, R.F.A. Moritz, N.T.Q. Anh, J. Ott, C. Sann, C. Sattler, M. Schädler, A. Schmidt, V. Tekken, D.T. Truong, K. Thonicke, M. Türke, T. Vaclavik, D. Vetterlein, C. Westphal, M. Wiemers, J. Settele, The LEGATO cross‑disciplinary integrated ecosystem service research framework: an example of integrating research results from the analysis of global change impacts and the social, cultural and economic system dynamics of irrigated rice production. Paddy and Water Environment PAWE 16(2)(2018) 287-319.https://doi.org/10.1007/s10333-017-0628-5. [19] G.M. Gurr, J. Liu, D.M.Y. Read, J.L.A. Catindig, J.A. Cheng, L.P. Lan, K.L. Heong, Parasitoids of Asian rice planthopper (Hemiptera: Delphacidae) pests and prospects for enhancing biological control by ecological engineering. Annals of Applied Biology 158(2) (2010) 149-176. [20] Langerwisch, F., Vaclavik, T., Bloh, W. v., Vetter, T.Thonicke, K., 2017, Combined effects of climate and land-use change on the provision of ecosystem services in rice agro-ecosystems, Environmental Research Letters 13(1), 015003. https://doi.org/10.1088/1748-9326/aa954d. [21] J.H. Spangenberg, K-L- Heong, A. Klotzbücher, T. Klotzbücher, N.T.Q. Anh, V. Tekken, D.T. Truong, M. Türke, J. Settele J., Doing what with whom? Stakeholder analysis in a large transdisciplinary research project in South-East Asia, Paddy and Water Environment PAWE 16(2)(2018) 321-337. https://doi.org/10.1007/s10333-018-0634-2. [22] M.H. Hoang, S. Namirembe, M. van Noordwijk, D. Catacutan, I. Öborn, A.S. Perez-Teran, H.Q. Nguyen, M.K. Dumas-Johansen, Farmer portfolios, strategic diversity management and climate-change adaptation – implications for policy in Vietnam and Kenya, Climate and Development 6(2)(214) 1-10. [23] K.L. Heong, L. Wong, J.H, de los Reyes, J. H., Addressing Planthopper Threats to Asian Rice Farming and Food Security: Fixing Insecticide Misuse, in: K.L. Heong, J. Cheng, M.M. Escalada (Eds), Rice Planthoppers: Ecology, Management, Socio Economics and Policy. Zhejiang University Press & Springer Science+Business Media, Hangzhou, China and Dordrecht, NL, 2015, 69 - 80. [24] G.M. Gurr, Z. Lu, H. Xu, P. Zhu, G. Chen, X. Yao, J. Cheng, Z. Zhu, J. L. Catindig, S. Villareal, H.V. Chien, L.Q. Cuong, C. Channoo, N. Chengwattana, L.P. Lan, L.H. Hai, J. Chaiwong, H.I. Nicol, D.J. Perovic, S.D. Wratten, K.L. Heong, Multi-country evidence that crop diversification promotes ecological intensification of agriculture. Nature Plants 2(2016), 16014. https://doi.org/10.1038/nplants.2016.14. [25] J.H. Spangenberg, J.-M. Douguet, J. Settele, K.L. Heong, Locked Into Continuous Insecticide Spraying in Rice. Developing an integrated ecological and socio-political DPSIR analysis, J Ecological Modelling 295(2015) 188–195, http://dx.doi.org/10.1016/j.ecolmodel.2014.05.010. [26] N. Phong, V.T. Thuy, A., Sookun, The application of the Framework for the Development of Environment Statistics (FDES 2013) in Vietnam, ENVSTATS News and Notes 34(2013) 19-20. [27] D.T. Truong, N.T.Q. Anh, N.T.N. Anh, Đ.K.K Ly, J.H. Spangenberg, J. Settele, V. Tekken, B. Rodríguez-Labajos, Policy Analysis Approaches in Implementing the Ecological Engineering in Vietnam: Experiences from LEGATO – An Interdisciplinary Project, VNU Journal of Science: Policy and Management Studies 32(1) (2016) 49-67. [28] Speth JG. 2019, A People’s State of the Nation. Common Dreams, March 29, 2019, https://voicesmotherearth.blogspot.com/2019/04/a-peoples-state-of-nation.html. [29] IPCC Intergovernmental Panel on Climate Change, Climate Change 2014: Impacts, Adaptation, and Vulnerability, IMO, UNEP, New York, Nairobi, 2014. [30] T.D. Vo, Household economic losses of urban flooding, Case study of Can Tho City, Vietnam. Asian Cities Climate Resilience Working Paper Series 12. International Institute for Environment and Development (IIED), London, UK, 2014. [31] P. Wester, A. Mishra, A. Mukherji, A.B. Shrestha, A. B. (Eds), The Hindu Kush Himalaya Assessment: Mountains, Climate Change, Sustainability and People, Springer Nature Switzerland Cham, Switzerland, 2019. [32] J.M. Maurer, J.M. Schaefer, S. Rupper, A. Corley, Acceleration of ice loss across the Himalayas over the past 40 years. Science Advances, 5(6), (2019). eaav7266. https://doi.org/10.1126/sciadv.aav7266 [33] J. Carew, L. Reid, L. Taylor, Natural Systems and Climate Change Resilience in the Lower Mekong Basin: Future directions for biodiversity, agriculture and livelihoods in a rapidly changing environment, International Centre for Environmental Management ICEM, Hanoi, Vietnam, 2014.